Evolution of lakes created by landslide dams and the role of dam erosion: A case study of the Jiajun landslide on the Dadu River, China. (1st February 2019) - Wu, L.Z.; Deng, H.; Huang, R.Q.; Zhang, L.M.; Guo, X.G.; Zhou, Y.
Abstract: During the Late Pleistocene, strong erosional riverine environments led to the widespread occurrence of landslides along the river valleys in southwestern China. Such landslides along the middle reaches of the Dadu River often caused large-scale dammed lakes. In this study, the typical large-scale Jiajun landslide and its associated dammed lake were investigated. The relatively complete sedimentary sequence of the lake was examined and multi-depositional characteristics were found. Analysis of the history of the dammed lake revealed the relationship between its formation and the river valley erosion. The evolution of the dammed lake was reconstructed based on changes of the sedimentary environments. We concluded that the lake experienced two stages of high-lake-level stable lacustrine sedimentation during this period, a two-stage large-scale dam breach, and retention periods lasting more than 100 years. The relationship between the formation of the ancient barrier lake and the river valley erosion in the middle reaches of the Dadu River is indicative of the erosive and depositional environments. The evolution of the ancient dammed-river landslide valley had considerable effect on valley erosion and the sedimentary environment of the Dadu River.